Abnormal Calcium Handling in Atrial Fibrillation Is Linked to Changes in Cyclic AMP Dependent Signaling - Franziska Reinhardt (MDPI AG, 2021)
Both, the decreased L-type Ca2+ current (ICa,L) density and increased spontaneous Ca2+ release from the sarcoplasmic reticulum (SR), have been associated with atrial fibrillation (AF). In this study, we tested the hypothesis that remodeling of 3′,5′-cyclic adenosine monophosphate (cAMP)-dependent protein kinase A (PKA) signaling is linked to these compartment-specific changes (up- or down-regulation) in Ca2+-handling. Perforated patch-clamp experiments were performed in atrial myocytes from 53 patients with AF and 104 patients in sinus rhythm (Ctl). A significantly higher frequency of transient inward currents (ITI) activated by spontaneous Ca2+ release was confirmed in myocytes from AF patients. Next, inhibition of PKA by H-89 promoted a stronger effect on the ITI frequency in these myocytes compared to myocytes from Ctl patients (7.6-fold vs. 2.5-fold reduction), while the β-agonist isoproterenol (ISO) caused a greater increase in Ctl patients (5.5-fold vs. 2.1-fold). ICa,L density was larger in myocytes from Ctl patients at baseline (p < 0.05). However, the effect of ISO on ICa,L density was only slightly stronger in AF than in Ctl myocytes (3.6-fold vs. 2.7-fold). Interestingly, a significant reduction of ICa,L and Ca2+ sparks was observed upon Ca2+/Calmodulin-dependent protein kinase II inhibition by KN-93, but this inhibition had no effect on ITI. Fluorescence resonance energy transfer (FRET) experiments showed that although AF promoted cytosolic desensitization to β-adrenergic stimulation, ISO increased cAMP to similar levels in both groups of patients in the L-type Ca2+ channel and ryanodine receptor compartments. Basal cAMP signaling also showed compartment-specific regulation by phosphodiesterases in atrial myocytes from 44 Ctl and 43 AF patients. Our results suggest that AF is associated with opposite changes in compartmentalized PKA/cAMP-dependent regulation of ICa,L (down-regulation) and ITI (up-regulation).